PENGARUH PENGETAHUAN FORMAL WAJIB PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Tyas Pambudi Raharjo; Licke Bieattant (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study is to determine the effect of the formal knowledge of taxpayers and taxpayer awareness on compliance of vehicle taxpayers in the institution of Samsat Polda in South Jakarta. The data used is primary data by distributing questionnaires to the Vehicle Taxpayer registered in the Office of South Jakarta Police Samsat. The populations that will be the object of research are all vehicle taxpayers registered in the Office of Samsat Polda in South Jakarta until the period of December 2016. The sampling technique used is accidental sampling. This research uses linear regression analysis method. The results of the research showed that the formal knowledge of taxpayers have a significant positive effect on compliance of vehicle taxpayers. The results of this study also concluded that the formal knowledge of taxpayers, and awareness of taxpayers significantly affect the compliance of vehicle taxpayers simultaneously.